Downregulation of TRPC4 and TRPC5 Inhibits Smooth Muscle Cell Proliferation without Affecting Endothelial Cell Proliferation - Wenjun Zeng; Yinan Ji; Haiping Zhang; Liusheng Chen; Li Du; Ruiwei Guo (Genetics Research)
Aims. The main treatment for coronary heart disease is percutaneous coronary intervention (PCI), and drug-eluting stents are designed to inhibit vascular smooth muscle cell (VSMCs) proliferation and migration causing restenosis by releasing pharmacological agents into the vessel wall. Once drug-eluting stents are deployed, these pharmacological agents exert many biological effects in the coronary circulation, not only inhibition of VSMCs but also extension to vascular endothelial cells (VECs). The purpose of this study was to explore target molecules that inhibit VSMCs proliferation without affecting VECs. Methods. mRNA and protein expressions of transient receptor potential channels (TRPCs) in cultured VSMCs and VECs were determined by western blotting and RT-qPCR. VSMCs and VECs proliferation was evaluated using CCK-8 assays and western blotting of proliferating cell nuclear antigen (PCNA). Calcium backfilling assays were performed to detect intracellular calcium ion concentration in cultured VSMCs and VECs. Results. The TRPC6 expression was more abundant in VECs than VSMCs, while TRPC4 and TRPC5 expressions were more abundant in VSMCs than VECs. Knockdown of TRPC4 or TRPC5 alone had no remarkable inhibitory effect on VSMC proliferation. Synergistic knockdown of TRPC4 and TRPC5 inhibited the proliferation of VSMCs, declined the expression of the PCNA, and reduced the intracellular calcium ion concentration but not VECs. Conclusion. These data suggest that concurrent inhibition of TRPC4 and TRPC5 inhibits VSMCs proliferation without affecting VECs, thus providing novel targets for developing pharmacological agents for drug-eluting stents.